PP.41.25: ROLE OF TEMPOL ON THE LEVEL OF OXIDATIVE STRESS AND GENE EXPRESSION IN HIGH SALT DIET FED SPRAGUE-DAWLEY RATS. (June 2015) - Cosic, A.; Novak, S.; Cavka, A.; Mihaljevic, Z.; Jukic, I.; Mihalj, M.; Drenjancevic, I.
Abstract : Objective: Previously, we demonstrated that 7 days of high salt (HS) intake down-regulated hypoxia inducible factor 1 alpha (HIF-1α) and cyclooxygenase 1 and 2 (COX1 and COX2) genes in the brain blood vessels (BBV) compared to control Sprague-Dawley (SD) rats fed standard rat chow (Physiology 2014 (London, UK), PCB177). HS diet suppresses the angiotensin II levels thus down-regulating all antioxidative enzymes genes which impairs antioxidative defense systems and increases oxidative stress. The aim of this study was to assess the effects of TEMPOL on the expression of antioxidative enzymes (Cu/Zn SOD, MnSOD, EC-SOD), COX 1, 2, HIF-1α, HIF prolyl hydroxylases (PHD1, PHD2 and PHD3), vascular endothelial growth factor (VEGF), inducible nitric oxide synthase (iNOS) and endothelial nitric oxide synthase (eNOS) in BBV. Design and method: Three groups of male SD rats were included in the study (N = 5 per group, age 11weeks) - control on a normal chow, HS (4%NaCl) and HS+TEMPOL (4% NaCl + TEMPOL 100 μmol/L in drinking water ad libidum). Following diet protocol, rats were anesthetized with ketamine (75 mg/kg) and midazolam (2.5 mg/kg) and sacrificed by decapitation and their BBV harvested. mRNA levels were determined by quantitative real-time PCR. Data were analyzed using t-test and p < 0.05 was considered significant. Results: There was significantly higher expression of EC-SOD, HIF-1α and VEGF in HS+TEMPOL group compared to both, control and HS group. Expression of COX2 and iNOS was significantly decreased in HS+TEMPOL compared to control group of animals. Expression of PHD1 was increased in HS + TEMPOL group in compared to HS group. Cu/Zn SOD and PHD3 gene expression was increased in HS+TEMPOL compared to both group, and expression of COX 1 and PHD2 in compared to HS group, but did not reach statistical significance. eNOS and MnSOD expression did not changed in compared to control or HS group. Conclusions: Our results show that expression of HIF-1α, VEGF and EC-SOD depends on the level of superoxide. Oxidative stress also affects the expression of COX-2 which is important in mediating functional vascular responses and may be a potential target, or gene interrelated with HIF-1α.